2016
DOI: 10.1007/s11273-016-9516-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and drivers for wetland connections in the Prairie Pothole Region, United States

Abstract: Ecosystem function in rivers, lakes and coastal waters depends on the functioning of upstream aquatic ecosystems, necessitating an improved understanding of watershed-scale interactions including variable surface-water flows between wetlands and streams. As surface water in the Prairie Pothole Region expands in wet years, surface-water connections occur between many depressional wetlands and streams. Minimal research has explored the spatial patterns and drivers for the abundance of these connections, despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 59 publications
0
46
0
1
Order By: Relevance
“…For example, Vanderhoof, Christensen, et al. () found that the average distance over which wetlands showed a surface‐water connection to streams varied substantially between ecoregions across the prairie pothole region. In areas dominated by flat, open basins and lakes, small changes in surface‐water levels can consolidate wetlands that were previously disconnected by distances >1 km (Vanderhoof and Alexander ).…”
Section: Factors Influencing Connectivitymentioning
confidence: 99%
“…For example, Vanderhoof, Christensen, et al. () found that the average distance over which wetlands showed a surface‐water connection to streams varied substantially between ecoregions across the prairie pothole region. In areas dominated by flat, open basins and lakes, small changes in surface‐water levels can consolidate wetlands that were previously disconnected by distances >1 km (Vanderhoof and Alexander ).…”
Section: Factors Influencing Connectivitymentioning
confidence: 99%
“…The PRMS depression storage essentially behaves as fill and merge, with fill and spill limited to periods of excessive storage (based on the dprst_dept_avg parameter [average depth of the surface‐water depression storage at maximum storage capacity for each HRU; Figure c]) making it more of a “merged, fill, and spill” conceptualization. Fill and merge can contribute to streamflow, expanding and merging with a stream‐intersect wetland (Vanderhoof, Christensen, & Alexander, ). As noted by Leibowitz et al (), fill and spill leads to more streamflow out of the basin, whereas fill and merge results in more internal basin storage.…”
Section: Methodsmentioning
confidence: 99%
“…; Vanderhoof et al. ) have all significantly increased our ability to characterize hydrologic fluxes between NFWs and other watershed components. These empirical characterizations are important for developing a fundamental understanding of the system in question (see Burt and McDonnell ) but are often limited in spatial domain and measurement period.…”
Section: Characterizing Hydrologic Connectivity Of Non‐floodplain Wetmentioning
confidence: 99%
“…), remotely sensed imagery to determine spatial and temporal patterns of wetland inundation (Vanderhoof and Alexander ; Vanderhoof et al. ), and water isotope analysis to examine potential contribution of wetlands to streamflow (Brooks et al. ).…”
Section: Characterizing Hydrologic Connectivity Of Non‐floodplain Wetmentioning
confidence: 99%